2017
DOI: 10.1038/sdata.2017.84
|View full text |Cite
|
Sign up to set email alerts
|

An imaging dataset of cervical cells using scanning near-field optical microscopy coupled to an infrared free electron laser

Abstract: Using a scanning near-field optical microscope coupled to an infrared free electron laser (SNOM-IR-FEL) in low-resolution transmission mode, we collected chemical data from whole cervical cells obtained from 5 pre-menopausal, non-pregnant women of reproductive age, and cytologically classified as normal or with different grades of cervical cell dyskaryosis. Imaging data are complemented by demography. All samples were collected before any treatment. Spectra were also collected using attenuated total reflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…ATR-FtIR and Raman spectroscopy were used to categorise disease and identify cancer or intra-epithelial neoplasia in a number of excised tissues, such as prostate [97-101], gastrointestinal tract [102][103][104][105][106], brain [95, 107,108], breast [109][110][111][112][113][114][115][116], lung [117,118] and skin [119][120][121]. Gynaecological applications include studies of cervical cytology and histopathology [122][123][124][125][126][127], ovarian cancer [128,129] and vulvar disease [130].…”
Section: Biospectroscopy For Endometrial Tissue Interrogationmentioning
confidence: 99%
“…ATR-FtIR and Raman spectroscopy were used to categorise disease and identify cancer or intra-epithelial neoplasia in a number of excised tissues, such as prostate [97-101], gastrointestinal tract [102][103][104][105][106], brain [95, 107,108], breast [109][110][111][112][113][114][115][116], lung [117,118] and skin [119][120][121]. Gynaecological applications include studies of cervical cytology and histopathology [122][123][124][125][126][127], ovarian cancer [128,129] and vulvar disease [130].…”
Section: Biospectroscopy For Endometrial Tissue Interrogationmentioning
confidence: 99%
“…ATR-FtIR and Raman spectroscopy were used to categorise disease and identify cancer or intra-epithelial neoplasia in a number of excised tissues, such as prostate [97][98][99][100][101], gastrointestinal tract [102][103][104][105][106], brain [95,107,108], breast [109][110][111][112][113][114][115][116], lung [117,118] and skin [119][120][121]. Gynaecological applications include studies of cervical cytology and histopathology [122][123][124][125][126][127], ovarian cancer [128,129] and vulvar disease [130].…”
Section: Biospectroscopy For Endometrial Tissue Interrogationmentioning
confidence: 99%
“…Presently, IR-FELs are open at many synchrotron-radiation facilities all over the world since the optical emission was first observed at a laboratory level more than 50 years ago [ 31 ]. Various original experimental studies using IR-FELs are reported as follows: ablation of biological tissues [ 32 , 33 , 34 ], alteration of biological functions [ 35 , 36 ], degradation of protein–metal complexes [ 37 , 38 ], optical and spectroscopic imaging [ 39 , 40 , 41 ], structural dynamics of biomolecules [ 42 , 43 ], chemical reactions in the gas phase [ 44 , 45 , 46 ], decomposition of biopolymers [ 47 , 48 , 49 ], nonlinear-optical physics [ 50 ], and observation of terahertz radiation [ 51 ].…”
Section: Introductionmentioning
confidence: 99%